Diabetes and driving. Issue 9 (17th February 2013) - Inkster, B.; Frier, B. M.
Abstract : The principal safety concern for driving for people treated with insulin or insulin secretagogues is hypoglycaemia, which impairs driving performance. Other complications, such as those causing visual impairment and peripheral neuropathy, are also relevant to medical fitness to drive. Case control studies have suggested that drivers with diabetes pose a modestly increased but acceptable and measurable risk of motor vehicle accidents compared to non‐diabetic drivers, but many studies are limited and of poor quality. Factors which have been shown to increase driving risk include previous episodes of severe hypoglycaemia, previous hypoglycaemia while driving, strict glycaemic control (lower HbA1c) and absence of blood glucose monitoring before driving. Impaired awareness of hypoglycaemia may be counteracted by frequent blood glucose testing. The European Union Third directive on driving (2006) has necessitated changes in statutory regulations for driving licences for people with diabetes in all European States, including the UK. Stricter criteria have been introduced for Group 1 vehicle licences while those for Group 2 licences have been relaxed. Insulin‐treated drivers can now apply to drive Group 2 vehicles, but in the UK must meet very strict criteria and be assessed by an independent specialist to be issued with a 1‐year licence.